Effect of the strengthened ribs in hybrid toughned kenaf/glass epoxy composites bumper beam - Makinejad, Majid Davoodi; Salit, Mohd Sapuan; Ali, Aidy; Ahmad, Desa (Marsland Press, 2012)
The growth of car production governs new environmental regulations “End-of Life Vehicles” (ELV) to enforce car manufacturer to substitute synthetic material to bio based materials. Low mechanical properties of natural fibre composite confine their application in automotive non-structural components. Hybridizations of kenaf with glass fibre along with epoxy PBT toughening did not completely fulfill the required impact property of the developed bio-composite bumper beam to substitute with typical material of the bumper beam glass mat thermoplastic (GMT). Therefore, in the first stage of the geometrical improvement “concept selection” concluded that the double hat profile (DHP) is the most suitable concept out of eight bumper beam concepts when six parameters with different weight are determined. In second trial, the usage of strengthen rib is employed to improve the impact property and performance of the bumper beam for utilization of hybrid kenaf/glass fibre as a car bumper beam.